anonymous
  • anonymous
What is the value of z for the equation fraction 1 over 2z = −fraction 3 over 4 + fraction 1 over 4z
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
−3 −1 1 3
Baby_Bear69
  • Baby_Bear69
1/2z = -3\4 + 1/4z ?
anonymous
  • anonymous
yes

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Baby_Bear69
  • Baby_Bear69
is z= -3 an option?
anonymous
  • anonymous
yes
anonymous
  • anonymous
The equation 2.2x − 4.4 = 1.8x can be transformed to form which of the following expressions? 0.4x = 4.4 4.0x = 4.4 0.4x = −4.4 4.0x = −4.4 @Baby_Bear69
Baby_Bear69
  • Baby_Bear69
A
Baby_Bear69
  • Baby_Bear69
do you want me to show my work?
Baby_Bear69
  • Baby_Bear69
|dw:1436990858652:dw|
anonymous
  • anonymous
can u help me with 2 more @Baby_Bear69
Baby_Bear69
  • Baby_Bear69
yeah but make another question please
anonymous
  • anonymous
Step 1: 2(y + 4) = 4y Step 2: 2y + 6 = 4y Step 3: 2y = 6 Step 4: y = 3 Which of the following explains how to correct Step 2 and shows the correct value of y? The equation should be y + 4 = 4y after division by 2; y = 5 The equation should be y + 4 = 4y after division by 2; y = 2 2 should be distributed as 2y + 8; y = 4 2 should be distributed as 2y + 8; y = 2
anonymous
  • anonymous
Step 1: 2(y + 4) = 4y Step 2: 2y + 6 = 4y Step 3: 2y = 6 Step 4: y = 3 Which of the following explains how to correct Step 2 and shows the correct value of y? The equation should be y + 4 = 4y after division by 2; y = 5 The equation should be y + 4 = 4y after division by 2; y = 2 2 should be distributed as 2y + 8; y = 4 2 should be distributed as 2y + 8; y = 2
anonymous
  • anonymous
@Baby_Bear69
Baby_Bear69
  • Baby_Bear69
idk sorry
anonymous
  • anonymous
ill become a fan @Baby_Bear69
Baby_Bear69
  • Baby_Bear69
i don't know it .-.

Looking for something else?

Not the answer you are looking for? Search for more explanations.